Association Between Neck Circumference and Preeclampsia In Pregnant Women - Apriyanti, Dwi; Budihastuti, Uki Retno; Kusnandar, Dan (International Journal of Human and Health Sciences (IJHHS), 2023)
The nutritional status of a person can be measured by neck circumference. This measurement uses a tape measure that is looped around the neck just below the larynx and perpendicular to the length of the neck. The parameters of neck circumference used to assess nutritional status are > 34 cm in women with BMI > 25 kg/m2 and > 36.5 cm in women with BMI > 30 kg/m2 with an accuracy rate of 99%. Being overweight and obese during pregnancy and childbirth will increase the risk of chronic disease in both mother and child. Pregnant women with obesity are at risk for pregnancy complications such as gestational hypertension, preeclampsia, gestational diabetes mellitus, and more often undergo cesarean delivery due to a baby born prematurely. An observational study with a case-control design using a cross-sectional approach was carried out by measuring neck circumference in 130 pregnant women with gestational age above 20 weeks which was divided into 65 respondents of pregnant women with preeclampsia and 65 respondents of pregnant women without complications. This research was conducted on pregnant women in Tangerang Regency. The chi-square test is used to analyze the data with a significant value of 0.05. The results of the Chi-Square test obtained a p-value of 0.000 (p<0.05), indicating a relationship between neck circumference and the occurrence of preeclampsia in pregnant women. The Contingency Coefficient value of 0.493 indicates the impact of obesity on the occurrence of preeclampsia by 49.3%, while other factors that influence preeclampsia are 50.7%. Neck circumference can be used as a method to assess nutritional status in pregnant women to prevent preeclampsia. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 139-143